1995
DOI: 10.1111/j.1600-0668.1995.t01-3-00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Linoleum. Part 1: Measurement of Volatile Organic Compounds by use of the Field and Laboratory Emission Cell, "FLEC"

Abstract: The volatile organic compounds (VOCS) emitted ji-om 12 linoleum samples were measured by use of the "Field and Laboratory Emission Cell" (FLEC) with sampling on Tenax TA followed by thermal desorbtion and GCIFID or GCIMS analysis, Major VOCs were alkanals, dkenals and fatty m&. The emissions were measured after 24 h in FLEC and again a&r one month's storage in a well ventilated mom.The emission proJils of hexand, nonanal and propanoic acid were modeled for four linoleum samples using a new exponential dafiion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 11 publications
4
26
0
Order By: Relevance
“…Some industrial processes have aldehydes as one of the raw materials and emissions may take place both in the manufacturing process and from use of the products. It has been reported that aldehyde emissions from building material are affecting indoor air quality [6][7][8][9][10]. Natural emissions of aldehydes from vegetation have also been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Some industrial processes have aldehydes as one of the raw materials and emissions may take place both in the manufacturing process and from use of the products. It has been reported that aldehyde emissions from building material are affecting indoor air quality [6][7][8][9][10]. Natural emissions of aldehydes from vegetation have also been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…One problem with linoleum is the unpleasant smell of lower quality grades. When the linoleum is in service, remnants of unsaturated fatty acids such as oleic and linoleic acid break down into a series of extremely strong smelling saturated and unsaturated aliphatic aldehydes (C5 -C10) and into analog carboxylic acids [87,88]. Even cork based floorings are not pure natural products but contain formaldehyde, phenol, furfural and toluene [89,90].…”
Section: Building Products and Room Furnishingsmentioning
confidence: 99%
“…Linseed oil paints [5,6], linoleum [7][8][9] and conventional water-based paints [10] may emit odorous volatile organic compounds (VOCs). The process of degradation may continue during the entire life of the product, i.e.…”
Section: Introductionmentioning
confidence: 99%